PERBEDAAN MANAGED FLOAT EXCHANGE RATE SYSTEM DAN FREELY FLOATING EXCHANGE RATE SYSTEM DI INDONESIA - Mudji Utami (Journal of Management and Business, 2003)
Consequence of the freely floating system and freely foreign exchange system, rupiah could he easily fluctuated, because exchange rate shift not in response but as governed by the interaction between supply and demand in the money markets. The supply and demand forces are influenced by the relative interest rate and relative of inflation. Thus this study examine whether there is a difference of magnitude in the influence of the relative interest rate and relative rate of inflation to the USD - IRD exchange rate when Indonesia adopts respectively the managed float exchange rate system and the freely floating exchange rate system. The finding shows at the level of confidence 95%, that there is no significant difference in the influence of the relative interest rate and relative rate of inflation to the USD - IRD exchange rates between both systems.